The influence of product quality, service quality and trust on costumer loyality in Honda Scoopy brand motorcycles PT. Hayati Pratama Mandiri - Andi Amri; Ramadhi (Marketing Management Studies, 2022)
This study aims to determine how much influence product quality, service quality and trust have on customer loyalty on Honda Scoopy motorcycles at PT. Hayati Scoopy Pratama Mandiri. The data collection method in this study was using a questionnaire, the population and sample in this study were 90 respondents. The results obtained based on the partial test (t test) obtained: (a) there is a positive and significant effect between product quality and customer loyalty. (b) there is a positive and significant effect between service quality and customer loyalty. (c) there is a positive and significant effect between trust and customer loyalty. Then based on the joint hypothesis test (F test) it can be seen that there is a positive and significant influence between there is a positive and significant influence between product quality, service quality and trust on customer loyalty. Keywords: Product Quality, Service Quality, Customer Loyality, Brand